Persepsi dan Respons Masyarakat terhadap Konflik Sosial dalam Era Digital - Nurul Hafifah Gea; Rahmaiya Rambe (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This research aims to understand how public perceptions and responses to social conflict are shaped in the digital era, marked by advances in information and communication technology. Using a descriptive qualitative approach and library research methods, this study analyzes various literature, journals, and previous research findings that address the relationship between digital media, social perceptions, and conflict dynamics. The results indicate that digital media plays a central role in shaping public perspectives on social conflict. Rapid, widespread, and interactive access to information makes it easier for people to engage in social issues, both actively through online campaigns and passively as observers. However, this phenomenon also poses challenges in the form of perceptual bias, the spread of hoaxes, and increased social polarization due to the dominance of certain narratives in the digital space. On the other hand, digital media also opens up opportunities for collective awareness, social empathy, and public participation in conflict resolution efforts. Therefore, improving digital literacy and media ethics are crucial factors in building a critical, rational, and peaceful society amidst the complexity of social interactions in cyberspace.